Role of Electronic Modules Based on Problem-Based Learning Model to Facilitate Critical Thinking Ability:A Systematic Literature Review - Ilda Asri; Hufri Hufri; Letmi Dwiridal; Selma Riyasni (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
Critical thinking is a 21st-century skill that students must master, especially in physics learning, which requires logical reasoning and problem-solving. However, students' critical thinking abilities remain relatively low. One solution proposed by many researchers is an electronic module (e-module) integrated with the Problem-Based Learning (PBL) model. This article aims to systematically examine the role of PBL-based e-modules in facilitating students' critical thinking through a Systematic Literature Review (SLR). The literature review previous studies on PBL-based e-modules across physics, chemistry, biology, and mathematics education, with physics contributing the largest share. A total of 15 journal articles were selected and review based on predetermined inclusion criteria. The findings show that e-modules developed using PBL syntax consistently improve students' critical thinking ability, with N-Gain scores in the moderate, high, and effective categories. These e-modules have also been reported as very valid and very practical for secondary school learning across all four subjects. The integration of real-world problems, active learning activities, and digital features enables students to analyze, evaluate, and solve problems more effectively. Therefore, PBL-based e-modules can serve as an innovative digital teaching resource to strengthen students' critical thinking ability and support student-centered learning in the digital era